A holistic approach to safe and eco-friendly driving in Indonesia from prospective psychology and technology: Literature-based exploration - Suryati Mahdalena Sianipar; Charli Sitinjak; Daniel Handoko (Universitas Muhammadiyah Banjarmasin, 2024)
Transportation is essential to daily life in Indonesia, supporting mobility, economic activity, and social connectivity. However, rapid urbanization and population growth have intensified challenges, including severe traffic congestion, high accident rates, and substantial contributions to carbon emissions. Traditional approaches to transportation management have proven insufficient to address these issues. This study aims to explore the role of psychological insights and technological advancements in fostering safer and more sustainable driving practices in Indonesia through a literature-based exploration. Data collection involved a structured review of academic publications, reports, and case studies published between 2010 and 2023, accessed from sources such as Scopus, Google Scholar, and institutional archives. Relevant studies were identified using keywords like